Sosialisasi Sistem Informasi Manajemen Dan Analisis Data Daerah Aliran Sungai (DAS) Terintegrasi Untuk Mendukung Rehabilitasi Lahan Dan Pengendalian Banjir Didas Desa Garoga - Noni Paisah; Erwina Azizah Hasibuan; Sahrul Harahap; Julianto Lubis (Jurnal Pengabdian kepada Masyarakat Radisi, 2026)
The flash flood that struck Garoga Village, Batang Toru District, South Tapanuli Regency, North Sumatra, on November 25, 2025, was one of the most severe hydrometeorological disasters in the region over the past three decades. The disaster caused 43 fatalities, displaced hundreds of residents, and cut off road access for 23 days. Studies indicate that the disaster was triggered by severe ecological degradation in the upper Batang Toru Watershed, including 72,938 hectares of deforestation between 2016 and 2024 and the absence of an integrated watershed monitoring system at the village level. This community service program aimed to implement a WebGIS-based Integrated Watershed Management Information System (SIMDAST), develop a participatory spatial watershed database, and strengthen community capacity in watershed monitoring and flood preparedness. Activities included field surveys, hydrological data collection, Sentinel-2 land cover mapping, WebGIS development, and participatory training involving 20 participants. SIMDAST was successfully implemented with five functional modules. Spatial analysis identified 138 hectares of critical land requiring rehabilitation, while forest cover remained only 31% of the watershed area. Furthermore, 87% of participants were able to operate the system independently, with knowledge scores increasing by 114.7%. SIMDAST proved effective in supporting community-based watershed management and improving flood preparedness.